The influence of different track surfaces and bicycles on mountain biking performance - Silveira, A.; Rama, L. (International Journal of Performance Analysis in Sport, 2020)
This study aims to evaluate the impact induced by different track surfaces and type of bicycles on the mechanical and physiological variables in mountain biker performance.